Impact of Goal-Directed Fluid Therapy on Postoperative Cardiac Complications and Biochemical Markers of Myocardial Stress in Elderly Patients Undergoing Major Non-Cardiac Surgery - Muhammad Awais, Faisal Toheed, Ahmad Naeem Kiani, Nusrat Ullah Khan, S. Iftikhar Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative cardiac complications remain a significant cause of morbidity and mortality among elderly patients undergoing major non-cardiac surgery. The peri-operative fluid management is important to sustain the haemodynamic stability and to minimise the cardiovascular stress. Goal-Directed Fluid Therapy (GDFT) has become an individualized method aimed at optimizing fluid therapy; however, the impact of GDFT on postoperative cardiac complications and biochemical markers of myocardial stress in elderly surgical patients is still to be evaluated. Objective: To determine if Goal-Directed Fluid Therapy reduces postoperative cardiac complications and biochemical markers of myocardial stress in the elderly patients undergoing major non-cardiac surgery. Methods: This prospective comparative clinical study was conducted from May 2022 to May 2023 at the Department of Cardiology, Rawalpindi Institute of Cardiology, Rawalpindi, Pakistan, and the Department of General Surgery, Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur, Pakistan. A total of 100 patients aged 65 years and above undergoing elective major non-cardiac surgery were enrolled and allocated into two groups: conventional fluid therapy (n=50) and Goal-Directed Fluid Therapy (n=50). Pre- and post-operative high sensitivity cardiac troponin-I (hs-cTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP) and creatine kinase-MB (CK-MB) levels were determined. The cardiac postoperative complications and recovery outcomes were documented and analyzed. Results: Patients managed with GDFT demonstrated significantly lower postoperative hs-cTnI (23.7 ± 8.6 vs. 35.6 ± 11.8 ng/L), NT-proBNP (421.5 ± 124.8 vs. 612.3 ± 172.6 pg/mL), and CK-MB levels (23.4 ± 6.7 vs. 32.1 ± 8.4 U/L) compared with conventional therapy (p<0.001). Myocardial injury (8.0% vs. 24.0%), atrial fibrillation (6.0% vs. 20.0%), major adverse cardiac events (6.0% vs. 18.0%), and ICU admissions (12.0% vs. 28.0%) were significantly lower in the GDFT group. Hospital stay was also shorter among patients receiving GDFT (6.4 ± 2.1 vs. 8.7 ± 2.8 days, p<0.001). Conclusion: Goal-Directed Fluid Therapy has a major effect on reducing myocardial stress, postoperative cardiac complications and hospital stay in elderly patients undergoing major non-cardiac surgery. It may have a beneficial effect on perioperative cardiac outcome and speed up postoperative recovery in high-risk surgical patients. Keywords: Goal-Directed Fluid Therapy; Elderly Patients; Myocardial Stress; Cardiac Complications; NT-proBNP; Non-Cardiac Surgery.